Future Trends in Smart Green IoV: Vehicle-to-Everything in the Era of Electric Vehicles - Tasneim Aldhanhani; Anuj Abraham; Wassim Hamidouche; Mostafa Shaaban (IEEE Open Journal of Vehicular Technology)
The electrification of the transportation sector is a pivotal stride towards ensuring sustainability in our systems. This paradigm offers a promising solution to multiple challenges, including reducing oil consumption, lowering Greenhouse Gas (GHG) emissions, enhancing air quality, improving the efficiency of the transportation sector, and facilitating the integration of renewable energy resources into the electric grid. Despite its potential, the electrification of vehicles encounters a major bottleneck-the need for diverse charging infrastructure options. Three groundbreaking technologies, including Dynamic Wireless Charging (DWC), Battery Swapping Stations, and Fast Charging Stations (FCSs), have emerged, holding the promise to accelerate the adoption of Electric Vehicles (EVs). These technologies address critical challenges such as range anxiety and charging downtime, contributing to a seamless experience for EV users. This work primarily delves into the realm of FCS, recognized as one of the most readily available options in the current market. Optimizing the utilization of charging infrastructure hinges on tackling challenges related to routing EVs to the nearest FCS capable of meeting specific charging requirements. These requirements encompass factors such as wait time, charging duration, and charging cost. In addition to the integration of Vehicle-to-Everything (V2X) communications for enhancing EV routing to FCS, coordinated management of EV charging demand becomes imperative for achieving grid load balancing and preventing grid overload. This paper aims to present the vision and future trends of Smart Green Internet of Vehicles (IoV) in the era of EVs. The focus extends beyond mere vehicular connectivity, delving into sustainable V2X connectivity, grid integration, vehicular networking, data security, and associated services.